The impact of lay counselors on HIV testing rates: quasi-experimental evidence from lay counselor redeployment in KwaZulu-Natal, South Africa. (10th September 2018) - Hu, Janice; Geldsetzer, Pascal; Steele, Sarah Jane; Matthews, Philippa; Ortblad, Katrina; Solomon, Tsion; Shroufi, Amir; van Cutsem, Gilles; Tanser, Frank; Wyke, Sally; Vollmer, Sebastian; Pillay, Deenan; et al.
Abstract : Objectives: This study aimed to determine the causal effect of the number of lay counselors removed from a primary care clinic in rural South Africa on the number of clinic-based HIV tests performed. Design: Fixed-effects panel analysis. Methods: We collected monthly data on the number of lay counselors employed and HIV tests performed at nine primary care clinics in rural KwaZulu-Natal from January 2014 to December 2015. Using clinic-level and month-level fixed-effects regressions, we exploited the fact that lay counselors were removed from clinics at two quasi-random time points by a redeployment policy. Results: A total of 24 526 HIV tests were conducted over the study period. Twenty-one of 27 lay counselors were removed across the nine clinics in the two redeployment waves. A 10% reduction in the number of lay counselors at a clinic was associated with a 4.9% [95% confidence interval (CI) 2.8–7.0, P  < 0.001] decrease in the number of HIV tests performed. In absolute terms, losing one lay counselor from a clinic was associated with a mean of 29.7 (95% CI 21.2–38.2, P  < 0.001) fewer HIV tests carried out at the clinic per month. Conclusion: This study provides some evidence that lay counselors play an important role in the HIV response in rural South Africa. More broadly, this analysis adds some empirical support to plans to increase the involvement of lay health workers in the HIV response.